A large congenital atrial septal defect in an adult with delayed therapy. Issue 3 (March 2021) - Xie, Xia; Tang, Mi; Kahn-Krell, Asher; Qin, Kele; Yang, Jinfu; Fan, Chengming
Patients with a large congenital atrial septal defect (ASD) traditionally have the ASD repaired at the preschool age. Unfortunately, insufficient education of patients regarding medical science and clinical recommendations can lead to delayed therapy, resulting in complications during adulthood. We report a rare case of a large congenital ASD in a 20-year-old man. Echocardiography showed a 67-mm ostium secundum defect and moderate mitral and tricuspid regurgitation. The patient underwent transthoracic ASD repair along with mitral and tricuspid valvuloplasty. This report emphasizes the importance of educating patients about congenital malformations and potential interventions in developing countries, particularly in rural communities.